اردو لطائف کا اولین مجموعہ:''لطائف ہندی''از للولال کوی (انیسویں صدی کی اشاعتوں کا تحقیقی تناظر): The First Collection of Urdu Jokes: ‘Lataif-e-Hindi’ By Lallu Lal Kavi (The Analytical Perspective of 19th Centaury's Editions) - Abbas Ahmar, Dr. Naseem (Zoraiz, 2024)
In 19th century, Fort William College played a vital pivotal to promote Urdu prose. Lallu Laal Kavi is a prominent name of this college who is the author of many books like Betal Pacheesi, Sanghasan Bateesi and Prem Sagar. His book ‘Lataif e Hindi’ is the earlier collection of humorist stories in Urdu, published in 1810 by Indian Press Calcutta. This article is a research base study of its different editions and comparative study of the criticism that was written about it in different times.